Investigation of Ar/CH₄ Mixtures in Dielectric Barrier Discharge: A Simulation Approach for Hydrogen Production - Amine, Nedjar Yahia Mohamed; Mohamed, Mostefaoui; Djilali, Benyoucef (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
This modeling study aimed to simulate hydrogen production through dielectric barrier discharge (DBD) in an argon-methane mixture at atmospheric pressure. Argon was selected as an additive due to its high ionization potential, which is expected to facilitate methane dissociation and enhance plasma reactivity. A series of simulations were conducted to assess the impact of varying argon concentrations (ranging from 0% to 90%) on hydrogen generation. A one-dimensional fluid model was employed to investigate methane conversion within the DBD reactor. This approach enabled a comprehensive evaluation of the effects of different Ar/CH₄ ratios, including pure methane, on reactor performance and key plasma characteristics, such as electron density, ion density, and species concentrations. The findings revealed that increasing the argon content significantly enhanced the ionization rate of methane and increased the discharge current, which directly correlated with higher electron density. Moreover, methane conversion efficiency and hydrogen production were found to be strongly dependent on the Ar/CH₄ ratio, with the highest hydrogen yield observed at a 50:50 argon-to-methane mixture. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).